Platforms of Work, Labour, and Employment Relationship: The Grey Zones of a Digital Governance - Dieuaide, Patrick; Azaïs, Christian (Frontiers in Sociology, 2020)
Based on observation of a sample of work platforms, this paper will focus on an analysis of the specific conditions in which the labour and employment relationship is organised and managed in these new productive worlds, now referred to as “platform capitalism”. How to define the employee/employer relationship in this world so far removed from the traditional frameworks of company organisation and operation? Can we still talk about an employment relationship when the employer is nothing more than a matching algorithm? What autonomy and what work are we talking about in the context of an employment relationship that is governed digitally? To address these questions, it would be reductive and dangerous to transpose the habitual framework of analysis for industrial relations onto the assessment of the practical, political and institutional conditions in which platform workers work, trade unions negotiate, businesses manage, and governments regulate. To carry out this analysis, we shall use the notion of the “grey zone ” (G.Z. in the figure above), a notion which simultaneously represents a departure from the norm and appears as the marker for a system of mediation and social relations with its own autonomy and dynamics. In the field of professional relationships, grey zones are not contemporaneous with digital platforms, but appeared long before with the crisis of Fordism, when the standard employment relationship was challenged and Taylor’s forms of organisation of labour within companies were rejected. Grey zones were numerous and persistent, evidence of the incomplete boundaries lodged at the very heart of the employment relationship and the division of labour. This paper analyses transformations in the employment relationship through the prism of the digital revolution. Whether intentional or not, this prescriptive power is a source of confusion, or a grey zone, in that in addition to being a service relationship, it is a relationship of influence that users must endure and in which they have no way of intervening. This is the theory that we put forward here.